Impact of Risk Committee on Climate Change Disclosure: The Moderating Role of Female Board - Priscilia, Joicelyn; Ivone, Ivone; Tang, Sukiantono (Journal of Governance, Taxation and Auditing, 2026)
This study examines the effect of the presence of a risk committee on climate change disclosure and investigates the moderating role of female board representation. The sample consists of 502 observations of non-financial companies that are listed on the Indonesia Stock Exchange (IDX) that consistently published sustainability reports during the period 2019–2023. Climate change disclosure is measured using eleven indicators based on the task force on climate-related financial disclosures framework. The analysis employs panel data regression analysis with a moderating variable. The results indicate that the presence of a risk committee alone does not have a significant effect on the level of climate change disclosure. However, companies with female board members exhibit significantly higher levels of climate change disclosure. Furthermore, the moderating analysis reveals that Female Board representation weakens the positive influence of the risk committee on climate change disclosure, suggesting an overlap in monitoring and oversight functions related to environmental issues. This study is motivated by the inconsistent adoption of climate change disclosure practices among Indonesian companies despite increasing regulatory pressure on sustainability reporting. The findings contribute empirical evidence from an emerging market context by integrating corporate governance mechanisms, gender diversity, and climate-related transparency, and provides practical implications for designing more effective governance structures to enhance the quality of climate change disclosure.